The Impact of Digital Storytelling-Based Learning Environment on Young Children's Science Process Skills - Ali A. Al-Barakat; Omayya M. Al-Hassan; Rommel M. AlAli; Nahla A. Ibrahim (Emerging Science Journal, 2025)
The present study aimed at examining the effects of digital storytelling-based learning environment on children's science process skills such as observation, classification and prediction. A total of 238 children were involved and divided into an experimental group which was exposed to digital storytelling and a control group which was not exposed to digital storytelling. The data collection included interactive digital stories and tests to assess science skills and semi-structured interviews to gather children's feedback. The findings of the study revealed that digital storytelling has a positive effect on children's scientific skills and this was because the experimental group performed better than the control group in all the skills assessed. There was a significant improvement in the observation skills of children in that they were able to identify more details in natural phenomena. The classification skills were enhanced since children were able to arrange and categorize information using the structure of digital stories. The prediction skills were also enhanced, which showed that there was an enhancement in the critical in thinking early skills. It is recommended that childhood-based curricula incorporate digital story, and teacher training should include it as well. Doi: 10.28991/ESJ-2025-SIED1-02 Full Text: PDF